2019
DOI: 10.2340/16501977-2587
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary rehabilitation for adults with neuromyelitis optica spectrum disorders: A pilot study

Abstract: The aim of this study is to investigate the effects of multidisciplinary rehabilitation for patients with neuromyelitis optica spectrum disorders who have moderate to severe disability. In 39 patients with neuromyelitis optica spectrum disorders, disability was assessed after 4 weeks of rehabilitation and 3 months of follow-up. In the patients who underwent multidisciplinary rehabilitation, bowel and bladder and motor functions (pyramidal and walking function) were improved compared with those with usual care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Therefore, there is no literature in this regard. However, concerning the impact of physical exercise on disability, the results of this section are in line with those of Suo et al [35], Khadem Al-sharia et al [36], and Soltani et al 2019) investigated the impact of a rehabilitation plan on neuromyelitis optica (an inflammatory disease that targets the optic nerves and spinal cord) and found out that physical disability of these patients was considerably improved.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, there is no literature in this regard. However, concerning the impact of physical exercise on disability, the results of this section are in line with those of Suo et al [35], Khadem Al-sharia et al [36], and Soltani et al 2019) investigated the impact of a rehabilitation plan on neuromyelitis optica (an inflammatory disease that targets the optic nerves and spinal cord) and found out that physical disability of these patients was considerably improved.…”
Section: Discussionsupporting
confidence: 83%
“…We considered that these results are due to the fact that the PT work exclusively in the ward, which enables close communication and increase the attention of the hospitalized patients to their motor functions. Moreover, many previous studies have reported that interactive communication plays an important role in improving patient outcomes 11 , 12 , 13 ) . In particular, physicians and medical social workers need to communicate well to shorten patients’ length of hospital stay (i.e., the period until they are discharged to their home or transferred to another hospital).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, physicians and medical social workers need to communicate well to shorten patients’ length of hospital stay (i.e., the period until they are discharged to their home or transferred to another hospital). Previous studies have reported that collaborations with interdisciplinary medical staff members are useful for improving the ADL level in patients 13 , 14 , 15 ) . Good communication and appropriate information sharing are important when multidisciplinary medical staff members are involved in patient care.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an MS case studies, multidisciplinary rehabilitation and fatigue management courses were found to improve functional levels and social participation (George and White, 2014). In a study of NMOSD, patients had improved bladder function and motor function and less fatigue after receiving multidisciplinary rehabilitation (Suo et al, 2019). However, the study only involved 4 weeks of intervention and 3 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%